O-9 What's the two-legged and one-legged vertical jumps limb symmetry in patients after acl reconstruction with a different time of postoperative physiotherapy attendance?. (18th November 2016) - Królikowska, Aleksandra; Czamara, Andrzej; Szuba, Lukasz; Kentel, Maciej; Krupa, Sebastian; Reichert, Pawel
Abstract : Objectives: Patients who want to return to pre injury recreational sport performance after anterior cruciate ligament reconstruction (ACLR) should restore specific motor abilities such as balance, lower limb symmetry in strength and power. Low to moderate intensity plyometric and landing technique drills are exercises for regaining jump abilities and improvement of intra-muscular and global coordination. Intensity and volume of these exercises should be dosed cautiously for ACLR patients in latter stages of postoperative physiotherapy. Limb symmetry index (LSI) between involved and uninvolved side lower than 5–10% is a good predictor for reducing risk of ACL reinjury. Assessment of relative load and LSI is possible by vertical ground reaction force (vGRF) measurements in two-legged or one-legged jumps. The purpose of the study was to assess two-legged and one-legged vertical jumps limb symmetry in patients after ACLR with a different time of postoperative physiotherapy attendance. Methods: Group I (n = 20) and the Group II (n = 15) consisted of patients after unilateral ACLR with the use of autologous ipsilateral hamstring graft. The time since ACLR in both groups was statistically insignificant (28 weeks in Group I and 32 weeks in Group II), however there were statistically significant differences between the time of postoperative physiotherapy attendance between the two groups (28 weeks in Group I and 11 weeks in Group II). The Group III consisted of 20 volunteers without known orthopaedic problems in history. In the three groups the measurements of vGRF during two-legged and one-legged vertical jumps were performed with the use of MTD-Balance system. Prior to the study the intra-rater and inter-rater test-retest reliability was carried out. In the three studied groups the LSI was calculated. One-way ANOVA and post-hoc Tukey's test were used to assess the significance of differences between LSI of three studied groups. Shapiro-Wilk test was performed to study the distribution normality. Additionally, for the intra-group comparison of vGRF values the Student's t-test was used. Results: The analysis didn't reveal any statistically significant differences in the one-legged jump LSI between the three studied groups (LSI = 98 in Group I, LSI = 94 in Group II, LSI = 99 in Group III), nevertheless there were found statistically significant differences in the two-legged vertical jump LSI. The statistically significant difference concerned the comparison between the Group II (LSI = 83) and Group III (LSI = 100). The difference between Group I (LSI = 99) and Group III was insignificant. The intra-group analysis didn't reveal any significant differences between involved and uninvolved leg in two-legged and one-legged jumps in Group I and in one-legged jump in Group II. Nevertheless, there were noted statistically significant differences between two legs in two-legged jump in Group II. Conclusions: In patients after ACLR who didn't undergo the half-yearly postoperative physiotherapeutic procedure the two-legged LSI was significantly different in comparison to individuals with no orthopaedic problems in history even though the one-legged vertical jumps LSI was similar in the three studied groups. The two last stages of postoperative physiotherapeutic procedure may have impact on regaining two-legged jump LSI in patients after ACL reconstruction on the level of healthy individuals.